ByzRev 08.2026.011: George E. Demacopoulos, Sacralizing Violence in Byzantium: Hymns, Empire, and the Narrowing of Christian Identity (Dumbarton Oaks Studies 51). Washington DC: Dumbarton Oaks Research Library and Collection 2025 - Tucker, Gregory (The Byzantine Review, 2026)
George E. Demacopoulos, Sacralizing Violence in Byzantium: Hymns, Empire, and the Narrowing of Christian Identity (Dumbarton Oaks Studies 51). Washington DC: Dumbarton Oaks Research Library and Collection 2025. VII, 244 pp. – ISBN 978-0-88402-523-8